Analysis the Effect of Corporate Social Responsibility Disclosure and Environmental Costs on Company Performance (Case Study on Mining Companies Subsector Coal Listed in Indonesia Stock Exchange) - Lim, Thalia; Frengky Situmorang (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to determine the influence of corporate social responsibility and environmental costs on company performance. This study uses a quantitative data method, The population in this study is coal companies listed on the Indonesia Stock Exchange totaling 33 companies. This study uses a purposive sampling method where from 33 companies are eliminated to 30 companies according to the criteria. Data testing was carried out by descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis tests. The results showed that the corporate social responsibility variable partially did not have a significant effect on the company's performance with a T value of 0.723 < T table 1.70113. Environmental costs partially have a significant effect on the company's performance with T calculated 2.888 > T table 1.70113. Corporate social responsibility and environmental costs have a significant simultaneous effect on the company's performance with an F value of 4.207 > an F value of 3.35 table with a sig value of 0.026 < 0.05. The regression coefficient value is 23.8%.